2013
DOI: 10.1186/1745-9974-9-26
|View full text |Cite
|
Sign up to set email alerts
|

Airway oxidative stress in chronic cough

Abstract: Background: The mechanisms of chronic cough are unclear. Many reactive oxygen species affect airway sensory C-fibres which are capable to induce cough. Several chronic lung diseases are characterised by cough and oxidative stress. In asthma, an association between the cough severity and airway oxidative stress has been demonstrated. The present study was conducted to investigate whether airway oxidative stress is associated with chronic cough in subjects without chronic lung diseases. Methods: Exhaled breath c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Exhaled breath condensate (EBC) concentration of 8-isoprostane reflects airway oxidative stress. It is higher in patients with chronic cough than in healthy subjects and, among the cough patients, correlates with the impairment in the cough-related quality of life [88]. In asthma, high concentration of 8-isoprostane in EBC is associated with poor cough-related quality of life and with the degree of cough responsiveness to dry air hyperpnoea.…”
Section: The Ability Of Cpthas To Differentiate Subjects With Asthma mentioning
confidence: 98%
“…Exhaled breath condensate (EBC) concentration of 8-isoprostane reflects airway oxidative stress. It is higher in patients with chronic cough than in healthy subjects and, among the cough patients, correlates with the impairment in the cough-related quality of life [88]. In asthma, high concentration of 8-isoprostane in EBC is associated with poor cough-related quality of life and with the degree of cough responsiveness to dry air hyperpnoea.…”
Section: The Ability Of Cpthas To Differentiate Subjects With Asthma mentioning
confidence: 98%
“…On the other hand, the increased oxidative stress pathways at baseline and induced by poly(I:C) in ASMC from chronic cough patients is of interest. It has been previously reported that increased airway oxidative stress is associated with chronic cough [ 24 ]. Recent work has indicated that oxidative stress, in particular downstream of mitochondrial dysfunction, activates airway nociceptive sensory nerves that may contribute to an excessive cough reflex [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it facilitates comparison of epidemiological results. Recent population-based studies and clinical trials utilise one of the aforementioned testing methods each: Sovij€ arvi [30][31][32][33][34][35][36][37], Malmberg [38][39][40][41] or Nieminen [14,[42][43][44]; the reference table may serve the purpose of offering comparisons in these example studies and others, or in future studies. Nowadays, the supply of histamine as a challenge test substance is very limited, therefore, a comparison to other challenge methods was also needed.…”
Section: Utilitymentioning
confidence: 99%